IN EACH OTHER WE (STRATEGICALLY) TRUST: THE DISCURSIVE NETWORKS OF TRUST IN TWITTER DISCUSSION OF IMMIGRATION IN AUSTRAILIA - Dehghan, Eshan (AoIR Selected Papers of Internet Research, 2019)
This study investigates the discourses around the topic of immigration in the Australian Twittersphere, especially with regards to the discursive role of trust in the dynamics of the debates. Methodologically, this paper draws from social media analytics, network analysis, corpus linguistics, and discourse-theoretical analysis. The findings show how Twitter users strategically and discursively use the platform’s affordances and choose who and what to trust, what hashtags to use, and what discourse to amplify, in order to both form agonistic networks of discursive alliances and to intensify antagonisms against the rival discourses. In this sense, the paper argues that trust, whether it is trusting the information sources or other users, becomes a discursive strategy employed in the hegemonic struggle over the issue of immigration in the Australian Twittersphere.